Directly Spun Epoxy‐Crosslinked Polyethylenimine Fiber Sorbents for Direct Air Capture and Postcombustion Capture of CO2. Issue 9 (28th July 2022) - Wilfong, Walter C.; Wang, Qiuming; Ji, Tuo; Baker, James S.; Shi, Fan; Yi, Shouliang; Gray, McMahan L.
Abstract : A novel, directly‐injected solid fiber sorbent is synthesized from a solvent‐stable, epoxy‐crosslinked basic immobilized amine sorbent (BIAS) for CO2 capture. Leach resistance of the BIAS organics toward 1‐methyl‐2‐pyrrolidone/H2 O (90/10, fiber solvent) reaches near 100% at the expense of CO2 capture and is achieved by increasing the extent of crosslinking. The optimized fiber sorbent, prepared with an N, N‐diglycidyl‐4‐glycidyloxyaniline/polyethylenimine (PEI)‐0.35/1 wt. ratio, retains 79.2% of PEI and captures 0.37 (direct air capture [DAC]) and 0.67 (postcombustion) mmol CO2 g‐fiber −1 . A nonoptimized prototype hollow fiber exhibits a stable 0.2 mmol CO2 g‐fiber −1 during DAC cycling and is assembled into a ten‐fiber module. These results demonstrate a large step toward practical application of this material. Abstract : Directly injected/spun fiber sorbents synthesized from solvent‐stable, crosslinked, immobilized amine sorbents remove CO2 under direct air capture (400 ppm CO2 ) and postcombustion (14% CO2 ) capture conditions. Scaleable fiber sorbents are a key milestone toward a viable hollow fiber rapid temperature swing adsorption system.